Individual Well-Being of the Elderly in Surabaya–Indonesia and Hangzhou–China - Setiasih; Adi Satria Indramawan; Xuejiao Chen (ANIMA Indonesian Psychological Journal, 2013)
Various researches indicate that the increase of age is not in parallel with the increase of well- being, similarly cultural pattern influences individual life quality. The problem revealed in this study was whether there is a (significant) difference between the well-being of elderly individuals in Surabaya-Indonesia and Hangzhou-China. The sample of this research (N = 193: Indonesia = 102, China = 92) is 60-year-old or over seniors, both men and women living in Surabaya and Hangzhou, collected by the incidental sampling technique. The collection of data was using Psychological Well-Being Scale (Diener et al., 2009). The result of this study shows that there is a significant difference of well-being between respondents in Surabaya and Hangzhou In general, there is a bigger opportunity to achieve the self-potentials of respondents in Hangzhou, making their well-being level higher than the respondents in Surabaya. Furthermore, the differences of the results are further discussed. Berbagai penelitian menunjukkan bahwa peningkatan usia tidak sejalan dengan peningkatan wellbeing, demikian pula pola-pola budaya memengaruhi kualitas hidup individu. Permasalahan yang diungkap dalam penelitian ini adalah apakah ada perbedaan wellbeing antara individu lanjut usia (lansia) di Surabaya-Indonesia dan di Hangzhou-Cina? Sampel penelitian ini (N = 193: Indonesia = 102, China = 92) lansia berusia 60 tahun atau lebih yang tinggal di Surabaya- Indonesia dan di Hangzhou-Cina, yang diambil dengan teknik incidental sampling. Pengumpulan data menggunakan Psychological Well-Being Scale (Diener et al.,2009). Hasil penelitian menunjukkan ada perbedaan well-being antara lansia di Surabaya-Indonesia dan di Hangzhou-Cina. Secara umum, dengan budaya yang berbeda lansia di Hangzhou mempunyai pengalaman dan cara yang berbeda dalam memenuhi kebutuhan, merealisasikan potensi maupun memberikan penilaian terhadap kualitas hidupnya. Selanjutnya dibahas perbedaan- perbedaan dalam hasil tersebut.